Práticas pedagógicas no contexto multisseriado da Educação Infantil em escolas do campo: Vila Pereira no Município de Barreirinha – Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The study, entitled Pedagogical practices in the multigrade context of early childhood education in rural schools in the: Pereira Village, city of Barreirinha, Amazonas, is linked to the Study and Research Group on Early Childhood Education (GPEDIN) of the Graduate Program in Science and Humanities Teaching at the Federal University of Amazonas (UFAM). The research sought to "analyze the pedagogical practices in multigrade classes in early childhood education in rural schools in the city of Barreirinha, Amazonas". To reach the general objective, we outlined the following specific objectives: to describe the trajectory of early childhood education in the field and its legislation; to get to know and record the different ways of organizing the pedagogical work developed by educators in multigrade classes in early childhood education in rural schools located in the municipality of Barreirinha, Amazonas; to provide moments of listening and dialogue with the educators from two rural schools about the pedagogical practices. This way, a case study was chosen, whose methodology is qualitative with observations and the use of the semi-structured interview technique (interview script), with the following as participant subjects: two kindergarten teachers, one pedagogue or teacher from the school, one field area coordinator, and the municipal secretary of education. The method adopted was Bardin's content analysis (1997). We analyzed books by researchers in the field, texts, dissertations, documents, regulations, and decrees at the national, state, and municipal levels that deal with early childhood education in the field, the pedagogical practices, and the multigrade classes. The results of the research indicate: schools with precarious infrastructure; teachers without higher education; a school curriculum the same as that used in urban schools, therefore out of context with the culture of the riverside children; in addition, pedagogical practices disconnected from the ambience of the region. The scenario observed during classroom observations shows the difficulty teachers face in developing lesson plans and implementing activities with children in multi-grade classes. The situation worsens when we encounter a lack of equipment and necessary pedagogical resources to ensure quality education for children in rural education. Due to this lack, teachers develop their work based on technical aspects, focusing on repetition and memorization of letters and numbers, thus curtailing the right to an education that values the cultural identity of the children living in the countryside and is a practice that transforms their lives. Despite all that was revealed in the research field, we still aim for better days by understanding that rural schools are also capable of building knowledge through successful pedagogical practices that contribute to the formation and education of children in the rural area of Barreirinha-AM.
Pedagogical practices in the multigrade context of Early Childhood Education in rural schools: Vila Pereira in the Municipality of Barreirinha - Amazonas
Keywords: Educação rural - Barreirinha (AM); Educação infantil; Classes multisseriadas - Educação; ENSINO DE CIENCIAS HUMANAS; Educação do campo; Crianças do campo; Classe multisseriada; Identidade; Amazonas; Field education; Early childhood education; Multigrade class; Identity; Amazon